أثر العقوبة الجزائية على المسار المهني للموظف - منصر ،سناء (جامعة الوادي University of El Oued, 2024)
إن القاعدة العامة هي استقلال العقوبة الجزائية عن العقوبة التأديبية ، فلكل منهما مجال تطبيق خاص به و غرض تسعى إلى تحقيقه ، و الاستثناء هو وجود ارتباط بينهما و هنا يظهر أثر الحكم الجزائي على الوضع الوظيفي للموظف في مساره المهني، و بما أن هذا الأثر يتجاذبه قانونين هما القانون الجزائي و القانون المنظم للوظيفة العمومية ، حاول المشرع من خلالهما توضيح الأثر المتبادل بين الجزائي و التأديب فيما يتعلق بوضعية الموظف الوظيفية ، و هو ما حاولنا التطرق له من خلال هذه الدراسة لموضوع أثر العقوبة الجزائية على المسار المهني للموظف في التشريع الجزائري. The general rule is the independence of the penal punishment from the disciplinary punishment, as each of them has its own field of application and a purpose that it seeks to achieve, and the exception is the existence of a connection between them, and here the effect of the penal ruling on the job status of the employee appears in his professional path, and since this effect is attracted by two laws They are the penal law and the law regulating public employment. Through them, the legislator tried to clarify the mutual impact between penal and disciplinary matters with regard to the employee’s job status, which is what we tried to address through this study of the topic of the impact of the penal ruling on the employee’s professional path in Algerian legislation
ماستر اعمال